Assessment of the Subarachnoid Hemorrhage International Trialists (SAHIT) Models for Dichotomized Long-Term Functional Outcome Prediction After Aneurysmal Subarachnoid Hemorrhage in a United Kingdom Multicenter Cohort Study. (18th November 2021) - Hostettler, Isabel C; Pavlou, Menelaos; Ambler, Gareth; Alg, Varinder S; Bonner, Stephen; Walsh, Daniel C; Bulters, Diederik; Kitchen, Neil; Brown, Martin M; Grieve, Joan; Houlden, Henry; Werring, David J
Graphical Abstract: